The gig economy - Ruyter, Alex de.; Brown, Martyn (Martyn David) (Newcastle upon Tyne : Agenda Publishing, 2019)
The "gig economy" is a relatively recent term coined to describe a range of working arrangements that have previously been denoted as precarious, flexible and contingent. Borrowed from musicians, a "gig" describes a one-night performance, but in the context of general employment, it covers the self-employed who work for hire, those on temporary, short-term contracts and on zero-hours contracts. In this concise overview, Alex de Ruyter and Martyn Brown explain the key facets of the gig economy and explore the dangers and potential it affords. Drawing on recent case-studies from the UK, Europe and the USA, it offers an authoritative guide through the theories and issues that surround the gig economy.
Introduction -- Theorizing the gig economy -- Working in the gig economy: international trends -- Regulation and lived experience of the gig economy -- Conclusions and implications: from wage economy to gig economy to automated ("no") economy.
Includes bibliographical references (pages 95-102) and index.
Keywords: Precarious employment; Industrial relations; Occupations; Self-employed.; Independent contractors; Labor market; Temporary employment